2015
DOI: 10.4274/jcrpe.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin as an Early Sign of Diabetic Kidney Injury in Children

Abstract: Objective:There is some evidence indicating that histopathological changes in type 1 diabetes mellitus (T1DM) emerge before onset of microalbuminuria. The aim of our study was to determine whether urine neutrophil gelatinase-associated lipocalin (NGAL) levels can be considered as an early sign of diabetic kidney injury.Methods:Urine NGAL (uNGAL) levels and urinary NGAL/creatinine ratio (uNGAL/Cr) were assessed in 76 patients with T1DM and compared with the findings of 35 healthy individuals. The relationship o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…Thus, the level of urinary NGAL appears to increase in the very early phase of T1DM before microalbuminuria develops. Patients with T1DM should be considered to have diabetic kidney injury from the time of diagnosis and preventive interventions should be initiated at an early stage to preclude the progression to end-stage renal disease [28]. Here, we found that the level of urine NGAL was significantly higher in the normoalbuminuria, microalbuminuria and macroalbuminuria groups compared with the control group, and found that urine NGAL was independently associated with albuminuria in T2DN.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, the level of urinary NGAL appears to increase in the very early phase of T1DM before microalbuminuria develops. Patients with T1DM should be considered to have diabetic kidney injury from the time of diagnosis and preventive interventions should be initiated at an early stage to preclude the progression to end-stage renal disease [28]. Here, we found that the level of urine NGAL was significantly higher in the normoalbuminuria, microalbuminuria and macroalbuminuria groups compared with the control group, and found that urine NGAL was independently associated with albuminuria in T2DN.…”
Section: Discussionsupporting
confidence: 57%
“…The urinary NGAL level (1.5-fold) already was significantly elevated in normoalbuminuric patients with diabetes compared with nondiabetic controls and was significantly associated with albuminuria [ 14 ]. Mean urinary NGAL and NGAL/creatinine ratio (NGAL/Cr) levels in both microalbuminuric and nonmicroalbuminuric diabetic patients were found to be higher than those in the controls, indicating that tubular involvement may precede glomerular involvement, as urinary NGAL levels are increased in the very early phase of diabetes before microalbuminuria develops [ 24 ].…”
Section: Neutrophil Gelatinase Associated Lipocalinmentioning
confidence: 99%
“…91 Similarly, elevated urinary NGAL is present in normoalbuminuric diabetic patients, as well as used to assess tubular lesions in the disease, 92 and has been shown to precede microalbuminuria in T1DM. 93,94 In addition, high values of this biomarker were noted in T2DM patients with normoalbuminuria which rose progressively in patients with microalbuminuria and macroalbuminuria. 95 Thus, urinary NGAL in T2DM patients likely has a role in predicting the evolution of disease.…”
Section: Tubular Biomarkersmentioning
confidence: 99%